2009
DOI: 10.1510/icvts.2009.208975
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous circumferential esophageal dissection in a young man with eosinophilic esophagitis

Abstract: Spontaneous esophageal dissection is a rare condition that may happen in patients with eosinophilic esophagitis. Conservative management is an important therapeutic option to be considered. We describe an unusual case of a young man with eosinophilic esophagitis who presented complaining of acute retrosternal pain, fever and vomiting. After a thorough evaluation including CT-scan and esophagogram, circumferential esophageal dissection and mediastinal abscess without visible perforation was observed. Abscess re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…15) Upon further review of the literature, we identified two recent reports linking eosinophilic esophagitis to esophageal dissections. 9,14) In both reports, the dissection was circumferential and associated with complications: perforation in one report and abscess formation in the other. To our knowledge, this is the first documented case of a noncircumferential esophageal dissection observed in a patient with eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15) Upon further review of the literature, we identified two recent reports linking eosinophilic esophagitis to esophageal dissections. 9,14) In both reports, the dissection was circumferential and associated with complications: perforation in one report and abscess formation in the other. To our knowledge, this is the first documented case of a noncircumferential esophageal dissection observed in a patient with eosinophilic esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…Management options for eosinophilic esophagitis involve diet restriction, medical management (systemic or inhaled corticosteroids, leukotriene receptor antagonists, proton pump inhibitors, and monoclonal antibodies), and endoscopic dilation when necessary. 9) Most patients respond well to treatment, and do not develop life threatening complications. Although uncommon, it is hypothesized that chronic eosinophilic infiltration may result in a friable esophageal mucosa and fragile wall which allows superficial lacerations to secondarily propagate into deeper esophageal layers resulting in dissection.…”
Section: Discussionmentioning
confidence: 99%
“…146,[152][153][154][155][156][157][158][159] Five postendoscopy perforations without preceding esophageal dilation were partial tears. [160][161][162] Of the 19 perforations reported, 7 patients required surgical intervention (ie, 4 primary repairs and 3 esophageal resections).…”
Section: Disease Complications Update Of 2007 Recommendationsmentioning
confidence: 99%
“…Four perforations were related to endoscope passage and seven were spontaneous perforations (Boerhaave's syndrome). [45][46][47][48][49][50][51][52][53] Cohen et al 49 reported the remaining three perforations, but it is unclear what intervention or clinical scenario precipitated them. There were no deaths reported in the literature from oesophageal perforations suffered in EoO patients.…”
Section: Safety and Potential Complicationsmentioning
confidence: 99%
“…Four perforations were related to endoscope passage and seven were spontaneous perforations (Boerhaave's syndrome). [45][46][47][48][49][50][51][52][53] Cohen et al …”
mentioning
confidence: 99%